The Role of Informal Digital Learning of English (IDLE) and Motivation in Enhancing Learners’ English Communication Skills - susanti, susanti (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
This inquiry explores the role of Informal Digital Learning of English (IDLE) and motivation in boosting learners’ English communication skills. The ubiquitous usage of digital technology facilitates students participating with English through social media, online videos, podcasts, games, and language learning applications outside academic hours. The current study was directed to the 2nd semester learners of the Information Systems program at STMIK Pontianak using a quantitative research design. Data were grouped through questionnaire, and speaking tests to explore learners’ experiences and the contribution of IDLE and motivation to their interaction proficiencies. The findings show that both receptive IDLE activity (RIA) and productive IDLE activity (PIA) provides precious exposure to authentic English use, increases motivation, and inspires learners’ autonomy. The frequent, supports, resources both (RIA) and (PIA) and digital tools used even learners’ autonomous motivation in learning language over time, it unconsciously influences learners’ speaking competences. It also helps bond formal classroom instruction with learners’ digital practices, making the learning process more pertinent and interesting.